Pojęcie ciała. Stanowisko Johna Locke’a - Grzeliński, Adam (Humaniora. Czasopismo Internetowe, 2019)
The article reconstructs the concept of body in the philosophy of John Locke; body is understood in a twofold sense: as a part of nature and as belonging to my own unique experience. Several threads interweave in the way Locke understands body: the historical method presenting the shaping of empirical concepts within human experience, the epistemological pessimism concerning the knowledge of real essences, and philosophical explication of religious truths which allows Locke to give his own interpretation of resurrection: the resurrection of bodies but not of souls, if they are to be understood as a substance independent from body. The analyses carried out on various planes: psychological description of human experience, natural philosophy, metaphysics and the philosophy of religion reveal the extent to which Locke’s philosophy is rooted in Cartesianism and shows how his empiricism overcomes it.